Description of a new species of Cottus Linnaeus (Cottidae) from the Western Dvina / Daugava River system, Baltic Sea basin, based on integrative taxonomy - Sideleva, Valentina G.; Zhidkov, Zakhar V. (Zootaxa, 2024)
In the genus Cottus (family Cottidae), 72 species are known. Of these, 37 species are found in North America, 17 in Asia, and 18 in Europe. Over the past 18 years, nine new species have been described from Western and Central Europe, two from Eastern part of this continent. Also, the validity of two Eastern European species was confirmed. In the Western Dvina / Daugava River system (Baltic Sea basin), Cottus dorofeevi sp. nov. was found. To describe this species, an integrative approach was used that combines morphological and molecular methods. The new species differs from other species of the genus Cottus by a combination of morphological characters. Taxonomically the most conspicuous features are: flattened shape of head; long pelvic fins (reaching anus); incomplete trunk canal of lateral line with 25-27 pores; presence of melanophores on ventral side of body and fins. Genetically, C. dorofeevi sp. nov. is sister to C. koshewnikowi. Haplotypes (CR) of C. dorofeevi sp. nov. are differentiated from haplotypes of other European species of the genus Cottus by genetic distances between 1.3% and 3%.